The Role of Further Vocational Education in Training the Competitive Specialists for the Regional Labor Market - M. M. Abragimovich (Образование и наука)
The paper demonstrates the rising importance of further education in the context of market economy. The fast changing reality of the postindustrial information society dictates the necessity of developing andmastering different models of further education. The problem of training and retraining the competitive domestic specialists has become even more urgent due to the membership of Russia in the International Trade Organization. The system of further education can become the key element in solving the aboveproblem providing the employees’ competence adaptation to the ever changing market demands.The research is aimed at studying the ways of improving the employees’ competitiveness in the secondary vocational institutions of the regional level, the competitive specialist concept being defined, organizational and pedagogical conditions facilitating the formation of such specialists denoted. The basic training model developed for the regional market is revealed along with its practical implementation in the Further Training Department of Novocherkassk State Industrial Humanitarian College. In the author’s opinion, the effectiveness of further education structures depends on the advancing educational content, formation of required professional competences, orientation on the personal development and individualization of educational process